1942
DOI: 10.3181/00379727-51-13858
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Action of Pyocyanine, Hemipyocyanine, Pyocyanase, and Tyrothricin

Abstract: ANTIMICROBIAL ACTION two limbs and followed by death. A small number of paralyzed hamsters survived, but developed atrophy and contractures of the affected muscles. The pathology in the infected hamsters is typical of poliomyelitis. The hamster strain is infectious for mice. Human convalescent poliomyelitis serum neutralized the hamster strain. Hamster convalescent serum neutralized the hamster OF ANTIBIOTIC AGENTS strain as well as the mouse strain. The hamster strain inoculated intracerebrally into 4 monkeys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1943
1943
2010
2010

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The only major exception occurred with P. aeruginosa, both in the in vitro simulated blood cultures and in rabbits with concomitant candidemia and bacteremia. One possible reason may be the ability of P. aeruginosa to produce pyocyanin, a compound which has been shown to inhibit the growth of C. albicans (10).…”
Section: Discussionmentioning
confidence: 99%
“…The only major exception occurred with P. aeruginosa, both in the in vitro simulated blood cultures and in rabbits with concomitant candidemia and bacteremia. One possible reason may be the ability of P. aeruginosa to produce pyocyanin, a compound which has been shown to inhibit the growth of C. albicans (10).…”
Section: Discussionmentioning
confidence: 99%
“…Since a concentrated solution of the toxic material was not prepared it was impossible to ascertain whether it was identical with that bacterial product which diffused through cellophan and induced hyphal tip branching in mixed fungal and bacterial culture. Stokes, Pick & Woodword (1942) found that I-hydroxyphenazine was more active against dermatophytes and Candida albicans than pyocyanine while the reverse was true for bacteria. My results show that Aspergillus terreus behaved like dermatophytes.…”
Section: A M a N G A Nmentioning
confidence: 97%
“…Therefore, antioxidant agents may also play a role in the regulation of growth and the composition of biofilms in H. panicea. Phytotoxic compounds and algicides may prevent the sponge from periphyton algae (53,104). An example of such a substance is oxazolomycin (produced by strain HB100).…”
Section: Discussionmentioning
confidence: 99%